Controlling perennial weeds in organically grown oats - Vanhala, Petri; Lötjönen, Timo; Hurme, Timo; Salonen, Jukka (MTT, 2004)
Perennial weeds are an increasing problem in Finland, particularly in organic farming. Mechanical control by hoeing, stubble cultivation and bare fallowing provides some options for managing these weeds. Mechanical control of perennial weeds in barley and oats was studied in a field experiment with five replicates, placed in a clay soil (containing 6 12% organic matter) field under organic production. The field was heavily infested with Sonchus arvensis and moderately infested with Cirsium arvense, Elymus repens and Stachys palustris. The treatments were (2001 2002) barley oats, barley oats with inter-row hoeing, and bare fallow oats, and additionally stubble cultivation (yes/no) across these treatments. The experiment was analyzed as a strip-plot design with stubble cultivation as a horizontal factor and treatment as a vertical factor. Weed number and dry mass were assessed prior to crop harvest from two 0.5 m × 0.5 m quadrats per plot. Both stubble cultivation in previous autumn and inter-row hoeing reduced significantly S. arvensis biomass in oats, but bare fallowing was the most effective treatment. Bare fallowing also controlled E. repens and S. palustris, but was not effective against C. arvense. Oat yields were slightly higher after bare fallow and slightly lower in hoeing treatment compared to ordinary oatsafter- barley crop stand, but the differences were not statistically significant. The results suggest that S. arvensis could be reduced by stubble cultivation in previous autumn, and could even be controlled by inter-row hoeing in oat stands. Bare fallow is an effective way to reduce most perennial weeds. When tackling perennial weeds in oat production, appropriate options for a given field and rotation should be chosen according to dominant weed species.
Keywords: Ka; kestorikkakasvit; kaura; Avena sativa; luonnonmukainen viljely; peltovalvatti; pelto-ohdake; juolavehnä; peltopähkämö; mekaaninen torjunta; perennial weeds; oats; Avena sativa; organic gardening; Sonchus arvensis; Cirsium arvense; Elymus repens; Stachys palustris; mechanical control